pH- and Calcium-Dependent Aromatic Network in the SARS-CoV‑2 Envelope Protein - Medeiros-Silva, João; Somberg, Noah H; Wang, Harrison K; McKay, Matthew J; Mandala, Venkata S; Dregni, Aurelio J; Hong, Mei (Journal of the American Chemical Society, 2022)
The envelope (E) protein of the SARS-CoV-2 virus is a membrane-bound viroporin that conducts cations across the endoplasmic reticulum Golgi intermediate compartment (ERGIC) membrane of the host cell to cause virus pathogenicity. The structure of the closed state of the E transmembrane (TM) domain, ETM, was recently determined using solid-state NMR spectroscopy. However, how the channel pore opens to mediate cation transport is unclear. Here, we use 13C and 19F solid-state NMR spectroscopy to investigate the conformation and dynamics of ETM at acidic pH and in the presence of calcium ions, which mimic the ERGIC and lysosomal environment experienced by the E protein in the cell. Acidic pH and calcium ions increased the conformational disorder of the N- and C-terminal residues and also increased the water accessibility of the protein, indicating that the pore lumen has become more spacious. ETM contains three regularly spaced phenylalanine (Phe) residues in the center of the peptide. 19F NMR spectra of para-fluorinated Phe20 and Phe26 indicate that both residues exhibit two sidechain conformations, which coexist within each channel. These two Phe conformations differ in their water accessibility, lipid contact, and dynamics. Channel opening by acidic pH and Ca2+ increases the population of the dynamic lipid-facing conformation. These results suggest an intricate aromatic network that regulates the opening of the ETM channel pore. This aromatic network may be a target for E inhibitors against SARS-CoV-2 and related coronaviruses.